2007
DOI: 10.1007/s11547-007-0148-2
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of small HCC through radiofrequency ablation and laser ablation. Comparison of techniques and long-term results

Abstract: We found LA and RFA to be equally effective. However, RA appears more suited to patients with small HCC nodules and in Child-Pugh class A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 22 publications
0
45
0
3
Order By: Relevance
“…Articles excluded after reading full text as failed inclusion/exclusion criteria n = 223 did not report loss to follow-up 37,39,42,43 . Owing to the differences in the nature of the interventions studied in the RCTs, double-blinding was virtually impossible.…”
Section: Four Trialsmentioning
confidence: 99%
“…Articles excluded after reading full text as failed inclusion/exclusion criteria n = 223 did not report loss to follow-up 37,39,42,43 . Owing to the differences in the nature of the interventions studied in the RCTs, double-blinding was virtually impossible.…”
Section: Four Trialsmentioning
confidence: 99%
“…The only randomized prospective study comparing laser ablation with RFA reported no significant difference in overall survival rates, with cumulative rates of 91.8%, 59.0% and 28.4% at one, three and five years respectively, without significant complications. However, a significantly better survival rate was reported for RFA in patients with Child-Pugh A stage disease [52] . Cryoablation uses the extreme cold of liquid nitrogen or argon gas to destroy abnormal tissue [53] .…”
Section: Other Ablative Therapiesmentioning
confidence: 95%
“…This technique can induce complete necrosis in HCC, but experience with it in HCC treatment is limited. In a trial comparing laser ablation to RFA, both were equally effective, although RFA was better suited to patients with small HCC nodules and in Child-Pugh class A [32]. The role of laser ablation in HCC still needs to be established.…”
Section: Laser Ablationmentioning
confidence: 99%